Relationship between Gadget Addiction and Sleep Disorder among Adolescents in the Community - Rohandi Baharuddin; Amrina Rasyada (CV. Get Press Indonesia, 2025)
The rapid advancement of digital technology has increased gadget use, particularly among adolescents. While gadgets offer benefits, excessive use can lead to negative consequences, including sleep disturbances. Quality sleep is crucial during adolescence, as it influences physical growth, learning concentration, and mental and emotional health. This study aimed to examine the relationship between gadget addiction and sleep disturbances in adolescents. A quantitative correlational approach was employed, using a questionnaire divided into two sections: gadget addiction and sleep disturbance, each with five Likert-scale items (1–5). The study population comprised adolescents aged 13–15 years at Junior High School N 31 Padang, with a sample of 100 respondents selected through purposive sampling based on predetermined criteria. Data were analyzed using the Pearson correlation test. The results indicated a significant positive correlation between gadget addiction and sleep disturbance (r = 0.61, p < 0.01), suggesting that higher levels of gadget addiction are associated with greater likelihood of experiencing sleep problems. The findings highlight the need for educational interventions from both schools and families to guide adolescents in managing gadget use and reducing the risk of sleep disturbances. In conclusion, gadget addiction is significantly related to sleep disturbances in adolescents, emphasizing the importance of promoting healthy and balanced technology use to support adolescent development.